Penerapan Demokrasi Di Lingkungan Gerakan Mahasiswa UNISMA Bekasi - ., Fadhilah; ., Nuraina (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
The title of this research is The Application of Democracy in the Environment of '45 Islamic University of Bekasi Student Movement Organization (Philosophical Review Toward Democracy in Perspective: Epistemology, Ontology, and Axiology). The background of this research is the change of perspective direction and democracy development in contemporary era that the characteristic leans to be cosmopolitan and liberal, especially since Reformation Government. The base theory of this research is the opinion of Dahl in Sorensen, George (2003) that title is Democracy and Democratization which explains about democracy principles.The purpose of this research is to know how the democracy comprehension and application in the environment of '45 Islamic University Student Organization is reviewed from three base aspects: Epistemology, Ontology, and Axiology. It uses mix method: which is hermeneutic and analysis-descriptive method. the benefits of this research are to increase university student's understanding toward democracy concept, essence and values of Pancasila democracy, to increase the sensitivity and become the guidance for politic attitude toward the democracy development in Indonesia. for UNISMA, it can be a base consideration in formulating the things related to right, obligation, and responsibility of university student organization movement.Achieved Result: 100 respondent are divided in three pattern/comprehension, namely: 31 respondents (31 %) understand the democracy substance as participant, control (supervision) and society preference to get country authority through its representative in political leadership, 38 respondents (38 %) understand democracy substance as the equality of right and obligation for all citizen, and 29 respondents (29%) understand democracy substance as the freedom for society to express their opinion in front of public. The democracy in UNISMA students organization movement is well from in term of concept. However, the problem is the splitting of ideology that underlying their democracy.